O letramento escolar na dinâmica das práticas de leitura e de escrita em uma sala de aula do 3º ano do 1º ciclo da rede municipal de Belo Horizonte - Viviane Maria Quintiliano Vianna (2019)
Reading, writing and literacy are constant subjects in the educational guidelines of the Municipal Education Network of Belo Horizonte. However, we note that there are still many gaps to be filled so that all the children can be reached at the end of the 3rd year of the 1st Cycle (goal established by the federal, state and municipal teaching systems) with the minimum competences, defined in the curriculum, related to reading and writing. In this direction, it is that this work has a general objective to analyze the dynamics of reading and writing practices lived in a class of the 3rd year of the 1st Cycle of the Municipal Network of Belo Horizonte and its relation with the theoretical presuppositions of literacy. The specific objectives were defined thinking of investigating the relations established between reading and writing and the teacher in his pedagogical work; as well as those established by students within and outside the school context. We searched through the literature review to discuss topics that could support the analyzes to be carried out later. The subjects chosen deal with issues related to the relationships established between schooling and literacy; literacy and reading; literacy, writing and orality; text, reading and writing. The field research took place between the months of March and September of 2018 and counted on our presence in the classroom through participant observation. Through the analysis of field notes, videos, photographs, interviews and documentary analysis, we try to treat the data collected in the light of literature review and other theoretical references consulted. The conclusions indicate that the teacher in her work with reading and writing can relate her practice to the theoretical presuppositions of literacy, resizing the planning done, whenever necessary. As for students and their relationship with reading and writing, the results show that the interest or not in carrying out the activities proposed by the teacher is related to the level of difficulty encountered in performing the requested task and that the parents, or responsible ones, support and encouragement regarding the accomplishment of the homework, as well as to the development of attitudes favorable to reading, are positive factors in the process of learning the language written by the child.